2011
DOI: 10.1007/s00535-011-0456-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of miR-144* as a novel fecal-based diagnostic marker for colorectal cancer

Abstract: We demonstrated that miRNAs are stable in the fecal microenvironment, and that, among them, miR-144* represents a novel fecal-based diagnostic marker for CRC screening. Nevertheless, our data need to be validated in a large cohort of subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 35 publications
5
89
0
1
Order By: Relevance
“…In addition, miR-144* and miR-106a were found to be significantly overexpressed in adenomas and in the stool of CRC patients compared with healthy individuals [86,89] . These studies have confirmed that miRNAs from stool samples require validation as diagnostic biomarkers for CRC.…”
Section: Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miR-144* and miR-106a were found to be significantly overexpressed in adenomas and in the stool of CRC patients compared with healthy individuals [86,89] . These studies have confirmed that miRNAs from stool samples require validation as diagnostic biomarkers for CRC.…”
Section: Markersmentioning
confidence: 99%
“…Many studies have been performed to quantify miRNAs in the blood for use as a biomarker (Table 4) [77][78][79][80][81][82][83][84][85][86][87][88] . miR-92a, located on chromosome 13q13, is a member of the miR-17-92 gene cluster.…”
Section: Mirna Biomarkers In Bloodmentioning
confidence: 99%
“…On the other hand, our data and others [25,27,28,[54][55][56][57][58][59][60][61][62][63][64][65][66] have shown that quantitative changes in the expression of few miRNA genes in stool or blood that are associated with colon cancer permit development of more sensitive and specific CRC molecular markers than those currently available on the market. In comparison to the commonly employed FOBT stool test, a noninvasive molecular and reliable test would particularly be more convenient as there would be no requirement for dietary restriction, or meticulous collection of samples, and thus a screening test would be acceptable to a broader segment of the population.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 55%
“…It should be emphasized that although not all of the shed cells in stool are derived from a tumor, data published by us and others [25,27,28,[56][57][58][59][60][61][62][63][64][65][66][67][68] have indicate that diagnostic miRNA gene expression profiles are associated with adequate number of exfoliated cancerous cells and enough transformed RNA is released in the stool, and also the availability of measurable amount of circulating. miRNA genes in blood (either cellular or extracellularly), which can be determined quantitatively by a sensitive technique such as PCR in spite of the presence of bacterial DNA, non-transformed RNA and other interfering substances.…”
Section: Current Methods For Colon Cancer Screeningmentioning
confidence: 98%
See 1 more Smart Citation